Caspases - Lazebnik, Yuri (Henry Stewart Talks, 2007)
What makes apoptotic cells alike?, What are caspases?, From the worm to humans, What is special about proteases?, What do blood clotting and apoptosis have in common?, How do caspases disassemble a cell?, How do you find out if caspases are active?, How are caspases activated?, What is left to learn?